On the Optimal Minimum Global Selection of Service Providers by Isolated Consumer Decision - Menegaz, Mauricio; Kalisewski, Luciano; Palma, Andrey; Alvares, Luis Otávio (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2007)
Complex phenomena can be studied by breaking them into smaller components and understanding the interactions between its parts. In this article, we propose a multi agent system that simulates the behavior of consumers and providers of services in an environment of concurrency. Each agent has its own preferences and makes his decision without communicating with the others. The isolate decision of each agent leads to a global emergent behavior where the minimum amount of providers that satisfy global demand is selected; potentially leaving unattended providers. The results provide useful insights for the resource allocation domain and suggest that the model developed may be useful in a wide range of problems involving multi agent self-organization.